The effect of recovery strategies on contractile properties using tensiomyography and perceived muscle soreness in professional soccer players - Rey, E.; Lago-Penas, C.; Lago-Ballesteros, J.; Casáis, L. (The Journal of Strength and Conditioning Research, 2012)
The capacity to recover from intense training and matches is considered an important determinant in soccer performance. At present, there is no consensus on the effect of posttraining recovery interventions on subsequent training session. The aim of this study was to determine the effectiveness of active (12 minutes of submaximal running and 8 minutes of static stretching) and passive recovery (20 minutes sit on a bench) interventions performed immediately after a training session on muscle contractile properties using tensiomyography (TMG) and perceived muscle soreness 24 hours after the training. During 2 experimental sessions, 31 professional soccer players participated in a randomized fully controlled trial design. The first session was designed to collect the player's TMG and muscle soreness measurements (pretest). After baseline measurements, the participants performed a standardized soccer training during which the heart rate (HR) and rating of perceived exertion (RPE) were recorded to evaluate the training load. At the end of training unit, all the players were randomly assigned to the active recovery group and the passive recovery group. A second experimental session was organized to obtain the posttest values. The players performed the same test, administered in the same order than in the first trial. The results showed that no differences between groups were observed in the HR and RPE. No significant effect because of recovery strategy was found on TMG parameters and perceived muscle soreness.